Evaluation of immunization status in patients with cerebral palsy: a multicenter CP-VACC study - Bozkaya-Yilmaz, Sema; Karadag-Oncel, Eda; Olgac-Dundar, Nihal; Gencpinar, Pinar; Sarioglu, Berrak; Arican, Pinar; Cavusoglu, Dilek (Springer, 2022)
Children with chronic neurological diseases, including cerebral palsy (CP), are especially susceptible to vaccine-preventable infections and face an increased risk of severe respiratory infections and decompensation of their disease. This study aims to examine age-appropriate immunization status and related factors in the CP population of our country. This cross-sectional prospective multicentered survey study included 18 pediatric neurology clinics around Turkey, wherein outpatient children with CP were included in the study. Data on patient and CP characteristics, concomitant disorders, vaccination status included in the National Immunization Program (NIP), administration, and influenza vaccine recommendation were collected at a single visit. A total of 1194 patients were enrolled. Regarding immunization records, the most frequently administrated and schedule completed vaccines were BCG (90.8%), hepatitis B (88.9%), and oral poliovirus vaccine (88.5%). MMR was administered to 77.3%, and DTaP-IPV-HiB was administered to 60.5% of patients. For the pneumococcal vaccines, 54.1% of children received PCV in the scope of the NIP, and 15.2% of children were not fully vaccinated for their age. The influenza vaccine was administered only to 3.4% of the patients at any time and was never recommended to 1122 parents (93.9%). In the patients with severe (grades 4 and 5) motor dysfunction, the frequency of incomplete/none vaccination of hepatitis B, BCG, DTaP-IPV-HiB, OPV, and MMR was statistically more common than mild to moderate (grades 1-3) motor dysfunction (p = 0.003, p < 0.001, p < 0.001, p < 0.00, and p < 0.001, respectively). Physicians' influenza vaccine recommendation was higher in the severe motor dysfunction group, and the difference was statistically significant (p = 0.029). Conclusion: Children with CP had lower immunization rates and incomplete immunization programs. Clinicians must ensure children with CP receive the same preventative health measures as healthy children, including vaccines.
Keywords: Cerebral palsy; Immunization status; Respiratory infections; Pneumococcus; Influenza